Perbedaan Umur Panen terhadap Hasil dan Mutu Benih Tanaman Buncis (Phaseolus vulgaris L.) - KADE LICANA LARASATI SURYAWAN; I GUSTI NGURAH RAKA; IDA AYU MAYUN; I KETUT ARSA WIJAYA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2019)
Difference in Harvest Age Against the Results and Quality of Seedlings of Beans(Phaseolus vulgaris L.) This study aims to determine the effect of seed age on the yield and quality of beans. This research is a one factor research with three different age of harvesttreatments are: harvest before physiological maturity 24 days after flower blooms,harvest at physiological maturity is 27 days after flower blooms, and harvest afterphysiological maturity is 30 days after flower bloom. This study used a randomizedblock design (RBD) with 9 replications. The observed variables included: thedevelopment of the seed wet weight, seed oven dry weight, seed moisture content, podand seed character, percentage of good seed, weight of 1000 seed grains, seedgermination, and seed growth simultaneity. The results showed that the pod harvesttime for the best seeds was carried out at the age of 27 days after the flowers bloomed. At that time the highest dry weight of the seeds and pods had changed color from greento yellowish green. At that time the seeds also showed maximum qualitycharacteristics, such as the percentage of good seeds (87.22%) and the weight of 1000seeds (91.34 g). Physiological characteristics of seed quality such as seed germinationcapacity of 99.78% and 88.78% simultaneity of seed growth were also obtained at thetime of pod harvest at 27 days after flower blooms.